Developing a Theory-Driven Serious Game to Promote Prescription Opioid Safety Among Adolescents: Mixed Methods Study - Abraham, Olufunmilola; Thakur, Tanvee; Brown, Randall (JMIR Publications, 2020)
BackgroundAdolescents in North America are severely affected by the opioid crisis, yet there are limited educational resources for educating teens about prescription opioid safety and misuse. Empirical literature lacks evidence regarding teen education about prescription opioid safety through serious games and lacks conceptual models and frameworks to guide the process of game development for this purpose. ObjectiveThis study aims to conceptualize and design a serious game prototype to teach teens about prescription opioid safety and propose a conceptual framework for developing a serious game to educate youth about safe and responsible use of prescription opioids. MethodsThe initial steps of the project comprised of the formulation of an integrated conceptual framework that included factors from health behavior models and game development models. This was followed by the formal process of serious game development, which resulted in a game prototype. The assessment of the game prototype was done through group discussions, individual interviews, and questionnaires with adolescents following gameplay. Field notes were used to keep track of the responses from the group discussions. Content and thematic analyses were used to analyze field notes and responses to the open-ended questionnaire, which were then used to refine the game prototype. ResultsA total of 10 playtests with over 319 adolescents and emerging young adults (AYAs) in community settings such as middle schools, high schools, and colleges were conducted by the project team between March and June 2019. The AYAs provided feedback on the initial game prototype using questionnaires administered through Qualtrics or in-person on paper. Preliminary feedback suggested that the teens found the game objectives, outcomes, and design appealing. Overall, the game was perceived as realistic, and learning outcomes seemed achievable. Suggestions for improvement included the need for additional direction on gameplay, clearer instructions, concise dialog, and reduced technical problems in the gameplay. ConclusionsWe propose a conceptual framework for developing a serious game prototype to educate youth about prescription opioid safety. The project used a theory-driven conceptual framework for the development of a serious game targeting the prevention of adolescent opioid misuse and garnered preliminary feedback on the game to improve the quality of gameplay and the prototype. Feedback through informal assessments in community settings suggests that the youth and their families are interested in a game-based approach to learn about prescription opioid safety in homes and schools. The next steps include modifications to the game prototype based on feedback from the community, integration of learning analytics to track the in-game behaviors of players, and formal testing of the final prototype.